2012
DOI: 10.1021/pr300846x
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR Study on the Short- and Long-Term Impact of Two Training Programs of Sprint Running on the Metabolic Fingerprint of Human Serum

Abstract: Metabonomics is an established strategy in the exploration of the effects of various stimuli on the metabolic fingerprint of biofluids. Here, we present an application of (1)H NMR-based metabonomics on the field of exercise biochemistry. Fourteen men were assigned to either of two training programs, which lasted 8 weeks and involved sets of 80-m maximal runs separated by either 10 s or 1 min of rest. Analysis of pre- and postexercise serum samples, both at the beginning and end of training, by (1)H NMR spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 44 publications
7
65
0
Order By: Relevance
“…Our results imply that when matched for overall effort and strain (RPE and HR peak ) the three endurance protocols may produce similar overall metabolic challenge and possibly similar muscular long-term adaptations [3][4][5]29 . This is in line with a recent study showing that two different sprint training programs consisting of maximal runs showed similar acute and long-term impact on serum metabolic fingerprint 14 . Thus, the overall metabolic response is mostly tied up to the overall effort and strain rather than to the characteristics (intensity, duration, work-rest transitions) of the endurance protocol per se.…”
Section: Global (Overall) Metabolic Responsesupporting
confidence: 93%
See 1 more Smart Citation
“…Our results imply that when matched for overall effort and strain (RPE and HR peak ) the three endurance protocols may produce similar overall metabolic challenge and possibly similar muscular long-term adaptations [3][4][5]29 . This is in line with a recent study showing that two different sprint training programs consisting of maximal runs showed similar acute and long-term impact on serum metabolic fingerprint 14 . Thus, the overall metabolic response is mostly tied up to the overall effort and strain rather than to the characteristics (intensity, duration, work-rest transitions) of the endurance protocol per se.…”
Section: Global (Overall) Metabolic Responsesupporting
confidence: 93%
“…Therefore, metabonomics is being increasingly used to examine the metabolic stress to a single exercise bout [7][8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Examples of metabolites that are highly affected by preanalytics and previously reported as biomarkers in various biomed-ical indications (11,(33)(34)(35)(36)(37)(38)(39) are serotonin, taurine, sphingosine-1-phosphate, glutamine, and glutamate (Fig. 2C, Fig.…”
Section: Discussionmentioning
confidence: 89%
“…More recently, in the NMR-based metabolomics-type of applications, increased circulating glycoproteins have been linked to rheumatoid arthritis and its severity (7 ) as well as to cardiovascular and cancer mortality (4 ). Differences in glycoprotein concentrations have also been seen during pregnancy (8 ), in relation to liver fibrosis (9 ), after exercise (10 ), and owing to long-term physical activity (11 ). Increased adiposity causally affects increased circulating glycoprotein concentrations (12 ).…”
mentioning
confidence: 99%